Disparities in sexual and reproductive health services utilization among urban and rural adolescents in southern Ethiopia, 2020: a comparative cross-sectional study - Aklilu Habte; Samuel Dessu; Biruk Bogale; Lire Lemma (BMC, 2022)
Abstract Background Although studies on the uptake of Adolescent sexual and reproductive health (ASRH) services in Ethiopia have been conducted they have failed to show the disparity in service uptake among rural and urban settings. Once the extent and determinants of ASRH service uptake in urban and rural contexts are known, it will be crucial to provide evidence-based information and recommendations for potential interventions to reduce the burden of disease and disability among adolescents. This study aimed at determining the level of SRH service utilization among urban and rural adolescents in the Guraghe zone, Southern Ethiopia. Methods A community-based comparative cross-sectional study was undertaken from November 1 -30, 2020. A multi-stage sampling technique was employed and a total of 1083 adolescents (361 from the urban and 722 from the rural areas) were selected randomly to take part in the study. Pre-tested, interviewer-administered, structured questionnaires were used to collect the data. The data were encoded and entered into Epi-Data version 3.1 and then exported to SPSS version 23 for analysis. χ2 test was computed to see a significant difference in SRH service utilization among urban and rural adolescents. In a bivariable logistic regression analysis, a variable with a p-value less than 0.25 has been selected for a multivariable logistic regression model. Variables with p-values less than 0.05 were declared statistically significant in multivariate logistic regression. Results A total of 1,075 adolescents (358 from urban and 717 from rural) took part in the study, yielding a response rate of 99.3%. The overall SRH service utilization among the whole adolescents was 39.5% (95%CI: 36.5, 42.4). There was a significant difference in SRH service utilization between urban 56.9% (95%CI: 51.8, 62.1) and rural 30.8% (95%CI: 27.4, 34.2) adolescents (χ2 = 68.3, p < 0.001). Residence[AOR = 2.62; 95%CI:1.63,3.41], availability of youth clubs [AOR = 4.73; 95%CI:3.43,6.53], taking part in peer education [AOR = 2.06; 95%CI:1.48,3.88], having parental discussion [AOR = 3.29; 95%CI:1.73,3.33], and being knowledgeable on SRH issues [AOR = 2.01; 95%CI: 1.45,3.03] were identified as a significant determinants of SRH service uptake. Having parental discussion, geographical accessibility, and knowledge on SRH were significant predictors of SRH service uptake among rural adolescents. Conclusion Overall, ASRH service utilization in the study area was low, despite urban adolescent service uptake becoming higher than rural adolescents. Since the majority of adolescents were enrolled in schools, schools should be an area of intervention to improve adolescents' knowledge of SRH services through mass media, community networks, and interpersonal/group communication. Furthermore, promoting parent-adolescent discussions, as well as peer-to-peer discussions at the family and school level, should be emphasized. Stakeholders in the education and health sectors need to strengthen their efforts to establish youth clubs in places where they do not yet exist, especially in rural schools.